Rattle-type Au@Cu 2−x S hollow mesoporous nanocrystals with enhanced photothermal efficiency for intracellular oncogenic microRNA detection and chemo-photothermal therapy - Cao, Yu (2019)
The coupling of the localized surface plasma resonance (LSPR) between noble metals of Au, Ag and Cu and semiconductors of Cu2 xE (E ¼ S, Se, Te) opens new regime to design photothermal (PT) agents with enhanced PT conversion efficiency. However, it is rarely explored on fabricating of engineered dual plasmonic hybrid nanosystem for combinatory therapeutic-diagnostic applications. Herein, rattle-type Au@Cu2 xS hollow mesoporous nanoparitcles with advanced PT conversion efficiency are designed for cellular vehicles and chemo-photothermal synergistic therapy platform. The LSPR coupling between the Au core and Cu2 xS shell are investigated experimentally and theoretically to generate a PT conversion efficiency high to 35.2% and enhanced by 11.3% than that of Cu2 xS. By conjugating microRNA (miRNA) gene probe on the surface, it can realize the intracellular oncogenic miRNA detection. After loading of anticancer drug doxorubicin into the cavity of the Au@Cu2 xS, the antitumor therapy efficacy is greatly enhanced in vitro and in vivo due to the NIR photoactivation chemo- and photothermal synergistic therapy. The rattle-type metal-semiconductor hollow mesoporous nanostructure with efficient LSPR coupling and high cargo loading capability will be beneficial to future design of LSPR-based photothermal agents for a broad range of biomedical application.